System Design of a 1 MW North-facing, Solid Particle Receiver. (May 2015) - Christian, J.; Ho, C.
Abstract: Falling solid particle receivers (SPR) utilize small particles as a heat collecting medium within a cavity receiver structure. The components required to operate an SPR include the receiver (to heat the particles), bottom hopper (to catch the falling particles), particle lift elevator (to lift particles back to the top of the receiver), top hopper (to store particles before being dropped through the receiver), and ducting. In addition to the required components, there are additional features needed for an experimental system. These features include: a support structure to house all components, calibration panel to measure incident radiation, cooling loops, and sensors (flux gages, thermocouples, pressure gages). Each of these components had to be designed to withstand temperatures ranging from ambient to 700 °C. Thermal stresses from thermal expansion become a key factor in these types of high temperature systems. The SPR will be housing ∼3000 kg of solid particles. The final system will be tested at the National Solar Thermal Test Facility in Albuquerque, NM.